Implementasi Perdagangan Intra-ASEAN: Menuju Integrasi Ekonomi Kawasan Pasca-MEA 2015 - Manggabarani, Najihah (Global and Policy Journal of International Relations, 2021)
AbstractIn 2007, ASEAN member states decided to accelerate the process of regional economic integration by advancing the implementation of the ASEAN Economic Community (EAC) from 2020 to 2015. Statistics from the ASEAN Secretariat in 2019 showed that intra-ASEAN trade in the 2015 AEC period did not increase consistently and tended to stagnate at 20-24 percent. Meanwhile in 2020, it is expected that intra-ASEAN trade can grow by up to 30 percent. This article aims to analyze why there is a phenomenon of inconsistency in the increase in intra-ASEAN trade during the 2015 AEC period taking into account domestic politics and economic interdependence of ASEAN countries. The methods used in this writing are qualitative methods that are analyzed descriptively. Data collection techniques are carried out through library studies, namely the acquisition of data from various sources both books, official news, articles, and other relevant documents. This study shows the results that ASEAN economic integration in addition to being influenced by domestic factors, is also influenced by the economic interdependence of ASEAN countries. Keywords: Regional economic integration, ASEAN Economic Community (AEC), intra-ASEAN tradePada tahun 2007, negara-negara anggota ASEAN memutuskan untuk mempercepat proses integrasi ekonomi regional dengan memajukan implementasi Masyarakat Ekonomi ASEAN (EAC) dari tahun 2020 hingga 2015. Data statistik dari Sekretariat ASEAN pada 2019 menunjukkan bahwa perdagangan intra-ASEAN pada periode MEA 2015 tidak meningkat secara konsisten dan cenderung stagnan di 20-24 persen. Sementara itu pada 2020, diharapkan perdagangan intra-ASEAN dapat tumbuh hingga 30 persen. Artikel ini bertujuan untuk menganalisis mengapa ada fenomena inkonsistensi dalam peningkatan perdagangan intra-ASEAN selama periode MEA 2015 dengan mempertimbangkan politik domestik dan saling ketergantungan ekonomi negara-negara ASEAN.Metode yang digunakan dalam tulisan ini adalah metode kualitatif yang dianalisis secara deskriptif. Teknik pengumpulan data dilakukan melalui kajian perpustakaan, yaitu perolehan data dari berbagai sumber baik buku, berita resmi, artikel, dan dokumen terkait lainnya. Studi ini menunjukkan hasil bahwa integrasi ekonomi ASEAN selain dipengaruhi oleh faktor domestik, juga dipengaruhi oleh saling ketergantungan ekonomi negara-negara ASEAN. Kata-kata kunci: Integrasi ekonomi regional, Masyarakat Ekonomi ASEAN (MEA), perdagangan intra-ASEAN  DOI : https://doi.org/10.33005/jgp.v9i2.3004